What influences a tourist to return to a cultural destination? - Vareiro, Laurentina (2019)
This study investigates the likelihood of tourists to repeat a visit to a cultural destination. We use a sample of 432 tourists who had visited Guimarães, Portugal. A cluster analysis separates visitors according to their opinion of the city's attributes. Afterward, a logistic regression analyses the variables that affect the likelihood of revisiting, taking into account the three clusters obtained. Results showed that, among the total sample, global quality of the destination had the biggest influence on the tourists' decision of whether to revisit the destination, whereas the least important reason was prior visits. These influential factors varied when different cluster group compositions were considered.